2002
DOI: 10.1002/ijc.10841
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of matrix metalloproteinase‐9 in operable non‐small cell lung cancer

Abstract: We assessed the clinical impact of MMP-9 expression on long-term survival in patients with operable non-small cell lung cancer (NSCLC). Primary tumors of 143 consecutive patients with NSCLC resected completely and without overt distant metastases (pT1-4, pN0-2, M0, R0) were examined for MMP-9 expression using immunohistochemistry with a polyclonal, affinity-purified rabbit antibody that recognizes both latent and active MMP-9. Immunohistochemical staining of tumor cells was evaluated in comparison to normal br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
2
3

Year Published

2003
2003
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 18 publications
8
62
2
3
Order By: Relevance
“…[4][5][6][7][8] Some immunohistochemical studies have shown that MMP-9 could have prognostic value in predicting long-term outcome in different types of tumors. 14,22,31,32 In our previous study, we reported that overexpression of MMP-9 immunoreactive protein in tissue section from primary tumors of head and neck carcinoma correlated with cause-specific and relapsefree survival. 22 There are, however, few previous publications report that serum MMP-9 would have any prognostic role in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Some immunohistochemical studies have shown that MMP-9 could have prognostic value in predicting long-term outcome in different types of tumors. 14,22,31,32 In our previous study, we reported that overexpression of MMP-9 immunoreactive protein in tissue section from primary tumors of head and neck carcinoma correlated with cause-specific and relapsefree survival. 22 There are, however, few previous publications report that serum MMP-9 would have any prognostic role in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Increased expression of MMP-2 and MMP-9 immunoreactive protein in various cancer tissues has been found to be associated with shortened survival and shortened relapse-free times in patients suffering from these cancers. [11][12][13][14] Recently, increased serum MMP-9 and MMP-2 levels have been reported to be practical in predicting disease prognosis in some types of tumors. [15][16][17][18] Several studies have shown that gelatinases are expressed in head and neck carcinoma cells, and gelatinases may take part in the progression and invasion of these tumors.…”
mentioning
confidence: 99%
“…As recently stated by Bonomi [28], a combined therapy with MMP-inhibitors agents should be limited to patients with MMP overexpression and pharmacological treatments should be tailored accordingly. For this type of treatment, the measurement of expression of the target MMP in tumor, in comparison to the adjacent non cancer tissue, may identify patients eligible for a specific MMP inhibitor therapy [19]. Even if an increased MMP mRNA expression may not be associated to an increased enzymatic activity, because of the necessity of the activation of MMP latent forms, an alteration of MMPs and TIMPs expression in cancer tissues could reflect an altered balance in the control of ECM, which is always a feature of malignant disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TIMP-1 has a selective binding with the pro-MMP-9 and is considered the main inhibitor for MMP-9 [13,15]. The detection of MMP9 expression has been performed in lung cancer by immunohistochemistry [1,7,[15][16][17][18][19], zymography [9,10,18,20], immunoenzymatic assays [21] and Northern analysis [8,15]. Increased plasma levels of MMP-9 protein were also detected in lung cancer patients [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…There were some discrepancies in the correlations between MMP-9 expression and tumor invasiveness in some tumor types. 33,[35][36][37][38] We noted a small number of instances of TIMP-1 expression among thymic epithelial tumors. The current study demonstrated that neither MMP-9 nor TIMP-1 plays a large role in the invasiveness of thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%